STRUKTUR KOMUNITAS GASTROPODA PADA EKOSISTEM MANGROVE DI PANCER CENGKRONG KABUPATEN TRENGGALEK - Ihsan Aditya; Wahyu Andy Nugraha (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTCommunity structure is a description of the condition of a community in a place cover, species composition, density type of dominant species, species diversity, and uniformity of type. Cengkrong mangrove forest is a conservation area which is used as a place of ecotourism. This study aims to determine the types of gastropods are found in ecosystems mangove Cengkrong, Knowing gastropods contained community structure in ecosystems mangove Pancer Cengkrong and mangrove density relationship with the density of gastropods in Cengkrong mangove ecosystem. This research is located in the Gulf of Prigi using three stations are Station 1 (density mangrove lower category), Station 2 (density mangrove medium category), and Station 3 (density mangrove high category), held for 3 days from 22 November to 25 November 2018. Data collection Gastropod using transect method squares 1 × 1 m2. Each different type of gastropods be sampled for the sake of identification types. Data retrieval is done in-situ water quality at each point of the test site and sediment sampling for further analysis of sediment types. Based on the analysis that has been carried out at three research stations in the mangrove ecosystem overall Cengkrong found 7 species of gastropods and 7 species of mangroves. Polynomial regression analysis has a moderate relationship between the density of mangrove gastropods density. Each different type of gastropods be sampled for the sake of identification types. Data retrieval is done in-situ water quality at each point of the test site and sediment sampling for further analysis of sediment types. Based on the analysis that has been carried out at three research stations in the mangrove ecosystem overall Cengkrong found 7 species of gastropods and 7 species of mangroves. Polynomial regression analysis has a moderate relationship between the density of mangrove gastropods density. Each different type of gastropods be sampled for the sake of identification types. Data retrieval is done in-situ water quality at each point of the test site and sediment sampling for further analysis of sediment types. Based on the analysis that has been carried out at three research stations in the mangrove ecosystem overall Cengkrong found 7 species of gastropods and 7 species of mangroves. Polynomial regression analysis has a moderate relationship between the density of mangrove gastropods density. Based on the analysis that has been carried out at three research stations in the mangrove ecosystem overall Cengkrong found 7 species of gastropods and 7 species of mangroves. Polynomial regression analysis has a moderate relationship between the density of mangrove gastropods density. Based on the analysis that has been carried out at three research stations in the mangrove ecosystem overall Cengkrong found 7 species of gastropods and 7 species of mangroves. Polynomial regression analysis has a moderate relationship between the density of mangrove gastropods density.Keywords : Community Structure, gastropods, mangrove ecosystem CengkrongABSTRAKStruktur komunitas merupakan gambaran mengenai kondisi suatu komunitas pada suatu tempat mencakup, komposisi jenis, kepadatan jenis dominasi jenis, keanekaragaman jenis, dan keseragaman jenis. Ekosistem mangrove Cengkrong merupakan kawasan konservasi yang dijadikan sebagai tempat ekowisata. Penelitian ini bertujuan untuk mengetahui jenis Gastropoda yang terdapat di ekosistem mangove Cengkrong, Mengetahui struktur komunitas Gastropoda yang terdapat di ekosistem mangove Pancer Cengkrong dan Hubungan kerapatan mangrove dengan kepadatan Gastropoda di ekosistem mangove Cengkrong. Penelitian ini berlokasi di Teluk Prigi dengan menggunakan tiga stasiun yaitu Stasiun 1 (kerapatan mangrove kategori rendah), Stasiun 2 (kerapatan mangrove kategori sedang), dan Stasiun 3 (kerapatan mangrove kategori tinggi), dilaksanakan selama 3 hari mulai 22 November – 25 November 2018.Pengambilan data Gastropoda menggunakan metode transek kuadrat 1×1m2. Setiap jenis Gastropoda yang berbeda diambil sampel untuk kepentingan identifikasi jenis. Pengambilan data kualitas perairan dilakukan secara insitu disetiap titik lokasi penelitian dan pengambilan sampel sedimen untuk selanjutnya dilakukan analisa tipe sedimen. Berdasarkan hasil analisis yang telah dilakukan pada tiga stasiun penelitian di ekosistem mangrove Cengkrong secara keseluruhan ditemukan 7 spesies Gastropoda dan 7 spesies mangrove. Hasil analisis regresi polinomial memiliki hubungan sedang antara kerapatan mangrove dengan kepadatan Gastropoda.Kata Kunci: Struktur Komunitas, Gastropoda, Ekosistem Mangrove Cengkrong